(untitled) (Journal of Applied Oral Science, 2009)
Two clinical cases in which Portland cement (PC) was applied as a medicament after pulpotomy of mandibular primary molars in children are presented. Pulpotomy using PC was carried out in two mandibular first molars and one mandibular second molar, which were further followed-up. At the 3, 6 and 12-month follow-up appointments, clinical and radiographic examinations of the pulpotomized teeth and their periradicular area revealed that the treatments were successful in maintaining the teeth asymptomatic and preserving pulpal vitality. Additionally, the formation of a dentin bridge immediately below the PC could be observed in the three molars treated. PC may be considered as an effective alternative for primary molar pulpotomies, at least in a short-term period. Randomized clinical trials with human teeth are required in order to determine the suitability of PC before unlimited clinical use can be recommended.